2018
DOI: 10.3892/ol.2018.7934
|View full text |Cite
|
Sign up to set email alerts
|

CEP55 promotes cell proliferation and inhibits apoptosis via the PI3K/Akt/p21 signaling pathway in human glioma U251 cells

Abstract: Abstract. Human glioma is one of the major malignancies worldwide with an increased mortality rate. Centrosomal protein of 55 kDa (CEP55) is an essential component of the CEP family and has been identified as a prognostic marker for multiple types of cancer. However, the function of CEP55 during glioma tumorigenesis remains unclear. In the present study, the data derived from the Oncomine database indicated that the expression of CEP55 is increased in glioma tissues compared with normal tissues. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…The CEP128 gene is related to the PI3K-Akt-mTOR signaling pathway. Centrosomal protein 128 ( CEP128 ) is part of the centrosomal protein family, including CEP55 that has been implicated in cancer progression [54]. Mutations within CEP128 have been associated with an aggressive type of lymphoma, the diffuse large B-cell lymphoma (DLBCL) [55].…”
Section: Discussionmentioning
confidence: 99%
“…The CEP128 gene is related to the PI3K-Akt-mTOR signaling pathway. Centrosomal protein 128 ( CEP128 ) is part of the centrosomal protein family, including CEP55 that has been implicated in cancer progression [54]. Mutations within CEP128 have been associated with an aggressive type of lymphoma, the diffuse large B-cell lymphoma (DLBCL) [55].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the down-regulation of CEP55 can inhibit the proliferation of breast cancer cells 23. CEP55 can promote proliferation and inhibit apoptosis of glioma cells through PI3K/Akt/p21 signal pathways 6. In addition, the expression of CEP55 is inversely correlated with poor prognosis in patients with advanced esophageal squamous cell carcinoma and NSCLC 24,25.…”
Section: Discussionmentioning
confidence: 99%
“…Centrosome-related protein CEP55 (centrosomal protein, 55 kD) is one of the coiled coil protein family members, and its main functions are to anchor the microtubule and polymerize related proteins, participate in the spindle formation, and then regulate cell proliferation 5. It has been found that CEP55 is expressed in both normal tissues and tumor cells and coupled with centrosomes and intermediates in the cell cycle which plays a role in regulating cell cycle after phosphorylation 6,7. In addition, CEP55 overexpression has been shown to be significantly correlated with tumor staging, invasiveness and metastasis of many malignant tumors,7,8 and can be used as a biomarker for tumor occurrence, progression and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…High CEP55 expression results in disordered cytokinesis and an increased number of unstable binucleated cells; these are oncogenic characteristics in tumorigenesis (34,35). Numerous studies have demonstrated that overexpression of CEP55 is associated with the pathological processes of several human malignances, including hepatocellular carcinoma (3638), colon carcinoma (39), breast cancer (4042), lung cancer (43,44), glioma (4547), nasopharyngeal carcinoma (48), oral cavity squamous cell carcinoma (49), osteosarcoma (50), head and neck cancer (51), anaplastic thyroid carcinoma (52), cervical cancer (53), esophageal squamous cell carcinoma (54,55), pancreatic cancer (56) and prostate cancer (57,58). In addition, high CEP55 expression in colorectal cancer downregulates the tumor susceptibility 101 gene in a post-transcriptional manner, and knockdown of CEP55 inhibits cell growth and increases apoptosis (39).…”
Section: Discussionmentioning
confidence: 99%